Interplay of dopants and native point defects in ZnO. Issue 10 (30th July 2013) - Brillson, L. J.; Zhang, Z.; Doutt, D. R.; Look, D. C.; Svensson, B. G.; Kuznetsov, A. Yu.; Tuomisto, F.
<x xml:space="preserve">Abstract</x> The controlled doping of ZnO required for a wide range of micro‐ and optoelectronic applications remains a major challenge. Recent studies of Li‐doped ZnO and degenerately Ga‐doped ZnO (GZO) reveal a systematic interplay between dopant incorporation and native point defects. Using the optical signature of Zn vacancies and their clusters to monitor their densities with growth conditions, processing and doping, we demonstrate that migration of Li and Ga into VZn sites plays a significant role in forming substitutional dopants and native point defects are actively involved in both donor and acceptor doping of ZnO.